IL-21 Increases the Reactivity of Allogeneic Human Vγ9Vδ2 T Cells Against Primary Glioblastoma Tumors. Issue 5 (June 2018) - Joalland, Noémie; Chauvin, Cynthia; Oliver, Lisa; Vallette, François M.; Pecqueur, Claire; Jarry, Ulrich; Scotet, Emmanuel
Abstract : Glioblastoma multiforme (GBM) remains the most frequent and deadliest primary brain tumor in adults despite aggressive treatments, because of the persistence of infiltrative and resistant tumor cells. Nonalloreactive human Vγ9Vδ2 T lymphocytes, the major peripheral γδ T-cell subset in adults, represent attractive effectors for designing immunotherapeutic strategies to track and eliminate brain tumor cells, with limited side effects. We analyzed the effects of ex vivo sensitizations of Vγ9Vδ2 T cells by IL-21, a modulating cytokine, on their cytolytic reactivity. We first showed that primary human GBM-1 cells were naturally eliminated by allogeneic Vγ9Vδ2 T lymphocytes, through a perforin/granzyme - mediated cytotoxicity. IL-21 increased both intracellular granzyme B levels and cytotoxicity of allogeneic human Vγ9Vδ2 T lymphocytes in vitro. Importantly, IL-21-enhanced cytotoxicity was rapid, which supports the development of sensitization(s) of γδ T lymphocytes before adoptive transfer, a process that avoids any deleterious effect associated with direct administrations of IL-21. Finally, we showed, for the first time, that IL-21-sensitized allogeneic Vγ9Vδ2 T cells significantly eliminated GBM tumor cells that developed in the brain after orthotopic administrations in vivo. Altogether our observations pave the way for novel efficient stereotaxic immunotherapies in GBM patients by using IL-21-sensitized allogeneic human Vγ9Vδ2 T cells. Abstract : Supplemental Digital Content is available in the text.